The Parasitic Infection in the common moorhen Gallinula chloropus Linnaeus, 1758 (Rallidae) from Basrah Governorate, Southern Iraq. - Al – Mansury , Hanan (Iraqi Journal of Aquaculture, 2025)
This study investigated parasitic infections in waterhen or swamp chicken the common moorhen (Gallinula chloropus). Samples were collected from various locations at Hammar marsh Basrah Province between January and December 2024. The findings revealed that 72.1% of the birds were infected with one or more parasite species, including Raillietina sp. and Hymenolepis sp. (tapeworms), as well as nematodes such as Capillaria sp., Ascaridia dissimilis, and Congylonema ingluricola. Seasonal variation in infection rates was observed, with the highest prevalence recorded during the colder months. Specifically, infection rates reached 42.85% in winter and 32.15% in spring. Mixed infections were predominant, occurring in 50% of the infected birds, while double infections were observed in 33.3%. Among the identified parasites, the nematode genus Capillaria exhibited the highest infection rate at 28.8%, followed by Raillietina spp. at 23.0%. These results highlight the significant parasitic burden in the common moorhen population in the Basrah region, particularly during colder seasons. The findings also emphasize the prevalence of mixed infections, suggesting possible ecological and environmental factors influencing parasite transmission dynamics in this wetland-dwelling bird species.